Bi2O3 modified TiO2 nanotube arrays and their application towards unsymmetrical dimethylhydrazine degradation in wastewater by electroassisted photocatalysis. Issue 5 (19th January 2023) - Zeng, YiZhi; Zhou, Feng; Gao, Yuan
Abstract : The preparation process parameters of TiO2 nanotube arrays (TNAs) prepared by anodic oxidation were systematically studied by the orthogonal experimental method. The TNAs were applied to bias potential assisted photocatalytic degradation of UDMH. Abstract : In the present research, the preparation process parameters of TiO2 nanotube arrays (TNAs) prepared by anodic oxidation were systematically studied by the orthogonal experimental method for the first time. Herein, the parameters of nine factors were optimized; the optimal parameters were: the electrolyte was a 0.2 mol L −1 NaF solution with 3% vol H2 O at pH 7, the anodic oxidation voltage was 40 V, the electrode spacing was 4 cm and the reaction was carried out for 60 minutes. The physicochemical properties of the materials were characterized by SEM, XRD, EDS, UV-vis, and PL spectroscopy. By electrodeposition of Bi2 O3 modified TNAs, the degradation rate of unsymmetrical dimethylhydrazine (UDMH) wastewater on the TNAs-10 was 89.14% within 10 h, which was 2.69 times that on pure TNAs. A bias potential of +0.3 V ( vs. open circuit potential) was applied to the modified TNAs-10. The degradation rate of UDMH was significantly enhanced on the TNAs-10 (bias) process as compared to the TNAs-10 process. The degradation rate of UDMH wastewater on TNAs-10 (bias) exhibited an exponential distribution. UDMH and its toxic by-products FDMH, NDMA were completely degraded after 8 h.